CASH MANAGEMENT POLICIES AND ACCOUNTABILITY AMONG FEDERAL MINISTRIES, DEPARTMENTS, AND AGENCIES IN ONDO STATE, NIGERIA - Adesanmi Timothy Adegbayibi; Toyin Emmanuel APEKO (Gusau Journal of Accounting and Finance, 2025)
Cash misappropriation allegations have rocked the public sector, and this has continued to threaten the accountability obligation of the government. To redeem their image, governments have continued introducing policies to reduce financial leakages and promote accountability in the management of public funds. This study, therefore, investigates the effect of cash management policies on accountability in federal Ministries, Departments, and Agencies (MDAs) in Ondo State, with a focus on policies such as the treasury single account system, the government integrated financial management information system, and the integrated personnel payroll information system.The study employed a primary data method through the administration of a questionnaire. The study adopted a survey research design to obtain information. The population of the study consists of 385 directors and heads of federal ministries, departments, and agencies in Ondo State with a sample size of one hundred and fifty (150) directors and heads of MDAs, which were selected using a purposive sampling technique because data for the study were directly obtained from the targeted respondents. The data were analyzed using descriptive statistics such as kurtosis, skewness, median, mean, standard deviation, and ordinary least square regression. The study's findings revealed that a treasury single account with a coefficient of 0.5703 and a p-value of 0.0000 positively affected accountability, and increased transparency led to an increase in federal MDA compliance. Government integrated financial information systems with a coefficient of 0.7115 and p-value of 0.0000 measures for cash management policies had a significant effect on accountability, and integrated personnel payroll information systems with a coefficient of 0.6301 and p-value of 0.000 positively impacted accountability.The study concluded that the treasury single account, government integrated financial information system, and the integrated personnel payroll information system significantly influence accountability. The study recommended that government authorities maintain treasury single account policies to increase government revenue because they have positively affected accountability. Also, several measures towards developing sound, effective and efficient government policy on TSA must be implemented in tandem with the Government Integrated Financial Management Information System (GIFMIS), Integrated Personnel Payroll Information System (IPPIS) for a sound public sector accounting system.